Personal Spending on Self-Education and Its Role in Achieving Economic Empowerment - Krim, Noura A.; Doub, Hajer A. (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
The study highlights the role of personal spending on self-education in achieving economic empowerment in Libya, using an analytical methodology and a survey. The results showed that 74% of participants do not work in government jobs, indicating a pressing need for employment opportunities. Meanwhile, 60% believe that training courses did not provide them with real job opportunities. The study confirmed the weak impact of self-education on economically empowering individuals, as 46% of participants indicated that the jobs they obtained were insufficient to secure sustainable income. On the other hand, the results indicated that spending on self-education was not economically beneficial for individuals in Libya, with 74% of participants reporting that they did not gain significant benefits from these investments. Among the areas of self-education spending, Quran memorization was the most common at 16%, while education in other fields remained limited. The study recommends increasing investment in vocational and technical education, developing self-education content to align with labor market needs, and providing electronic infrastructure to support online self-education.
Keywords: Private spending; Self-education; Economic empowerment; Job opportunities; Human capital